Piedra, tierra y madera - Montero Espina, Diego (2003)
<Casa B> en <La Rinconada>, Laguna Garzón, Maldonado, Uruguay, año 2000. Con terrazas de madera y construcción de piedra
Keywords: URUGUAY; MALDONADO; VIVIENDAS RURALES; VIVIENDAS DE VACACIONES; PIEDRA; MADERA